Adherence to climate change‐related ingroup norms: Do dimensions of group identification matter?. (9th June 2014) - Masson, Torsten; Fritsche, Immo
Abstract Recent research provides evidence that group norms influence intentions to engage in pro‐climate behaviour and that identification with the group moderates the norm effects. However, past studies have neglected to examine if the effects on norm adherence vary among different identification aspects. The present studies close this gap by investigating group‐level self‐investment (i.e. the importance of and satisfaction with the group) and self‐definition (i.e. perceived similarities among group members) as possible moderators of group norm effects. We used two experimental studies to test our assumption that self‐investment but not self‐definition would moderate the norm‐intention relation. The results support our assumption and show that group members who were highly self‐invested in the group (but did not necessarily perceive themselves as similar to other group members) adhered more strongly to climate‐related ingroup norms than less self‐invested group members. However, perceived similarity among group members (i.e. self‐definition) did not positively contribute to respondents' decision to conform to a group norm. Copyright © 2014 John Wiley & Sons, Ltd.